Efficacy and safety of janagliflozin monotherapy in Chinese patients with type 2 diabetes mellitus inadequately controlled on diet and exercise: A multicentre, randomized, double‐blind, placebo‐controlled, Phase 3 trial. Issue 5 (20th January 2023) - Ji, Linong; Jiang, Xiaozhen; Hao, Qingshun; Cheng, Zhifeng; Wang, Kun; Pang, Shuguang; Liu, Meiying; Guo, Yushan; Chen, Xiaowen; Su, Xiuhai; Ning, Tao; Liu, Jie; et al.
Abstract: Aims: To evaluate the efficacy and safety of janagliflozin, a selective renal sodium‐glucose cotransporter‐2 inhibitor, as monotherapy in drug‐naive Chinese patients with type 2 diabetes mellitus (T2DM). Materials and methods: This Phase 3 trial included a 24‐week, multicentre, randomized, double‐blind, placebo‐controlled period, followed by a 28‐week extension period. A total of 432 patients with glycated haemoglobin (HbA1c) levels ≥7.0% (53 mmol/mol) and ≤10.5% (91 mmol/mol) were randomized (1:1:1) to receive once‐daily placebo, 25 mg or 50 mg janagliflozin. After 24 weeks, patients on placebo were switched and re‐randomized (1:1) to 25 mg or 50 mg janagliflozin, whereas patients on janagliflozin maintained the initial therapy. The primary endpoint was change from baseline in HbA1c after 24 weeks. Results: At Week 24, the placebo‐adjusted least squares mean changes in HbA1c were −0.80% (95% confidence interval [CI] −0.98% to −0.62%)/−8.7 mmol/mol (95% CI −10.7 mmol/mol to −6.8 mmol/mol) and −0.88% (95% CI −1.06% to −0.70%)/−9.6 mmol/mol (95% CI −11.6 mmol/mol to −7.7 mmol/mol), respectively ( P <  0.001 for both). A higher proportion of patients achieved HbA1c <7.0% (53 mmol/mol) with janagliflozin 25 mg and janagliflozin 50 mg compared with placebo (47.2%, 49.3%, and 23.5%, respectively). Both janagliflozin doses significantly decreased fasting plasma glucose, 2‐hour postprandial glucose, body weight and systolic blood pressure, as well as increased high‐density lipoprotein (HDL) cholesterol and insulin sensitivity compared with placebo ( P <  0.05 for all). The trends in improvement of these variables were sustained during the 28‐week extension period. Overall incidences of adverse events were 67.8%, 71.5% and 60.7% with janagliflozin 25 mg, janagliflozin 50 mg and placebo, respectively. The incidence of urinary tract infections and genital fungal infections was low. No severe hypoglycaemia or ketoacidosis occurred. Conclusions: Janagliflozin 25 mg and 50 mg monotherapy once‐daily effectively improved glycaemic control, reduced body weight and blood pressure, improved HDL cholesterol and insulin sensitivity, and was generally well tolerated.